1991
DOI: 10.1111/j.1398-9995.1991.tb00634.x
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of histamine release from human basophil leucocytes: role of H1, H2 and H3 receptors

Abstract: A novel class of histamine receptors (H3), controlling histamine synthesis and release, was described in rat and human brain and peripheral nerve endings. The present study was undertaken to evaluate whether H3 receptors contribute to the regulation of histamine release from human basophils. Basophil leucocytes were incubated with a H3 antagonist (thioperamide; concentrations ranging from 1 nM to 10 microM) or with a H3 ((R)alpha methyl-histamine; concentrations ranging from 1 to 100 mM), and subsequently were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…Activated basophils release stored histamine using a degranulation mechanism. Histamine affects many cells (for review see [42,43]) and even the basophils themselves by binding with the H2 receptors (H2R) [44][45][46] and by mediating the reregulation of further histamine release. This negative regulation mechanism on anti-IgE-activated basophils ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Activated basophils release stored histamine using a degranulation mechanism. Histamine affects many cells (for review see [42,43]) and even the basophils themselves by binding with the H2 receptors (H2R) [44][45][46] and by mediating the reregulation of further histamine release. This negative regulation mechanism on anti-IgE-activated basophils ( fig.…”
Section: Discussionmentioning
confidence: 99%
“…Since total cellular histamine is low, the extent of such an early release would be limited, as shown in Table 2 by the absolute amount of released histamine lower at pre-treatment than at 21 days post-treatment, thus preventing the onset of hypersensitivity reactions after treatment. Additionally, any such early in vivo release of histamine may down-regulate further release through an autocrine mechanism involving H2 receptors [27]. …”
Section: Resultsmentioning
confidence: 99%
“…Human basophils have been proven to have H2-recep tors, stimulation of which elevates the intracellular levels of cyclic 3',5'-adenosine monophosphate to inhibit anaphylactic histamine release (18). In addition, it has been reported that cimetidine enhances the release by a blockade of the receptor (19). Furthermore, in human lung mast cells, anaphylactic histamine release is also demonstrated to be blocked by stimulation of their H2 receptor (20).…”
Section: Histamine Levels In Rat Plasmasmentioning
confidence: 93%